Heart Transplantation in a 14-Year-Old Boy in the Presence of Severe Out-of-Proportion Pulmonary Hypertension due to Restrictive Left Heart Disease: A Case Report - Martin Schwienbacher; Ulrich Schweigmann; Nikolaus Neu; Elisabeth Schermer; Corinna Velik-Salchner; Ina Michel-Behnke; Erentraud Irnberger; Christina Maria Steger; Jörg Ingolf Stein; Ralf Geiger (Case Reports in Cardiology)
A 14-year-old boy after balloon valvuloplasty of severe aortic valve stenosis in the neonatal period was referred for heart-lung transplantation because of high grade pulmonary hypertension and left heart dysfunction due to endocardial fibroelastosis with severe mitral insufficiency. After heart catheterization, hemodynamic parameters were invasively monitored: a course of levosimendan and initiation of diuretics led to a decrease of pulmonary capillary wedge pressure (from maximum 35 to 24 mmHg). Instead of an expected decrease, mean pulmonary artery pressures (mPAP) increased up to 80 mmHg with increasing transpulmonary pressure gradient (TPG) up to 55 mmHg. Oral bosentan and intravenous epoprostenol then led to a ~50% decrease of mPAP (TPG between 16 and 22 mmHg). The boy was listed solely for heart transplantation which was successfully accomplished 1 month later.